Nonlinear statistical modeling proceedings of the thirteenth International Symposium in Economic Theory and Econometrics : essays in honor of Takeshi Amemiya - Amemiya, Takeshi; Hsiao, Cheng 1943-; Morimune, Kimio; Powell, James 1955- (Cambridge University Press, 2001)
This collection brings together important contributions by leading econometricians on (i) parametric approaches to qualitative and sample selection models, (ii) nonparametric and semi-parametric approaches to qualitative and sample selection models, and (iii) nonlinear estimation of cross-sectional and time series models. The advances achieved here can have important bearing on the choice of methods and analytical techniques in applied research.